Coronary risk categories and achievement of LDL-cholesterol goals in an adult population in Trujillo, La Libertad, Peru, 2007 - Huamán Saavedra, Juan J. (2018)
Introduction: The Expert Panel on Detection, Evaluation and Treatment of High Blood Cholesterol in Adults established LDL cholesterol as the primary target of therapy.Objective: To determine the frequency of coronary risk categories and reaching LDL cholesterol goals according to age and sex in adult individuals in Trujillo.Materials and methods: 123 women and 123 men randomly selected were placed in the following age groups: 20 to 39, 40 to 59 and 60 to 79 years old. A clinical examination was performed, and glucose and lipids profile were measured using enzymatic methods.Results: Coronary risk categories were as follows: low, 73,98; moderate, 5,28 %; moderately high, 11,79 %; and high, 8,94 %. High and moderately high risks were more frequently found in the 60 to 79 year-old group (26.83 % and 20.8%, respectively, p<0,0004) and in male subjects (p= 0.045). LDL cholesterol goals were achieved by 67,89% of subjects, with no difference according to gender, and this percentage decreased to 53,76% in the 60 to 79 year-old group. Also, 53.76%, 76.92%, 61.54%, 51,72% and 18,18% of subjects with low, moderate, moderately high, and high coronary risk achieved LDL cholesterol levels, respectively. Only 12,5% of diabetic subjects also did so. Age, hypertension and diabetes rates, as well as total cholesterol and LDL cholesterol concentrations were significantly higher in those subjects not achieving LDL cholesterol goals. 43.8% of all subjects achieved LDL cholesterol goals.Conclusions: The frequency of higher coronary risk categories increases with age and in male subjects. 67,89 % of all subjects achieved LDL cholesterol levels, regardless of gender, and this rate diminished with age.